2007
DOI: 10.1007/s12034-007-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and thermally stimulated discharge conductivity (TSDC) study in polymer thin films

Abstract: The electrical conductivity of naphthalene doped polystyrene (PS) films (≈ 61⋅58 μm thick) was studied as a function of dopant concentration and temperature. The formation of charge transfer (CT) complexes and strong concentration dependence of carrier mobility point out that the current carriers are transported through doped polymer system via hopping among sites associated with the dopant molecules. The activation energy, E a , was calculated from the graph of logσ vs 10 3 /T plot within low and high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 7 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…8(a and b) shows the plots of Log (r) and Log (f) at a frequency range of 42 Hz to 1 MHz with a temperature range of 303 K to 433 K. The rise of electrical conductivity with an increase of frequency is common for semiconductor and polymeric materials. This is might be due to the fact that, as the dopant concentration is increased, the dopant molecules start bridging the gap separating the two localized states and lowering the potential barrier between them, thereby facilitating the transfer of charge carrier between two localized states [33]. The behavior of the curves clearly indicates an increase in the conductivity with increasing of the temperature.…”
Section: Ac Electrical Conductivitymentioning
confidence: 98%
“…8(a and b) shows the plots of Log (r) and Log (f) at a frequency range of 42 Hz to 1 MHz with a temperature range of 303 K to 433 K. The rise of electrical conductivity with an increase of frequency is common for semiconductor and polymeric materials. This is might be due to the fact that, as the dopant concentration is increased, the dopant molecules start bridging the gap separating the two localized states and lowering the potential barrier between them, thereby facilitating the transfer of charge carrier between two localized states [33]. The behavior of the curves clearly indicates an increase in the conductivity with increasing of the temperature.…”
Section: Ac Electrical Conductivitymentioning
confidence: 98%
“…In case of solids, the absorption of photons could also occur for photon energies lesser than or equal to the energy gap, hν ≤ E opt due to the presence of tail states in the forbidden gap. The absorption coefficient at the photon energy below the optical gap (tail absorption) depends exponentially on the photon energy and obeys the Urbach relation 36 given as…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The obtained data revealed that the optical energy band gap decrease significantly with increasing nano Cr 2 S 3 concentration, which may be explained on the basis of the fact that the incorporation of small amounts of dopant forms charge transfer complexes in the host matrix (Abdullah, et al 2013). These charge transfer complexes increase the electrical conductivity by providing additional charges, this result in a decrease of the optical energy band gap, by facilitating the transfer of charge carrier between the localized states (Abdelrazek, et al, 2013;Sangawar, et al, 2007). The width of the localized tail states in the forbidden gap (Urbach tail), is an indicator of the defect levels in the forbidden band gap (El-Khodary, 2010).The absorption coefficients just below the fundamental gap can be used to calculate the Urbach energy using following relations (Urbach 1953):…”
Section: Resultsmentioning
confidence: 99%